2021
DOI: 10.3389/fmicb.2021.653027
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Olive Saplings and Organic Amendments on Soil Microbial Communities and Effects of Mineral Fertilization

Abstract: Plant communities and fertilization may have an impact on soil microbiome. Most commercial olive trees are minerally fertilized, while this practice is being replaced by the use of organic amendments. Organic amendments can both fertilize and promote plant growth-promoting organisms. Our aims were (i) to describe the changes in soil bacterial and fungal communities induced by the presence of young olive trees and their interaction with organic amendments and (ii) to compare the effects of mineral and organic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 103 publications
(116 reference statements)
1
6
0
1
Order By: Relevance
“…In current study, the sum of relative abundances of Ascomycota and Basidiomycota reached 72.39 to 95.90% across all revegetation stages (Table 2). This result aligned with earlier studies, which revealed that Ascomycota and Basidiomycota are the most ubiquitously dominant phyla in soil fungal communities (Bello et al, 2021;Llimós et al, 2021;Nuñez et al, 2021). There was an obvious transition at the phylum level which showing that the relative abundance of Basidiomycota steadily increased, while the relative abundance of Ascomycota gradually decreased along with natural revegetation (Table 2).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In current study, the sum of relative abundances of Ascomycota and Basidiomycota reached 72.39 to 95.90% across all revegetation stages (Table 2). This result aligned with earlier studies, which revealed that Ascomycota and Basidiomycota are the most ubiquitously dominant phyla in soil fungal communities (Bello et al, 2021;Llimós et al, 2021;Nuñez et al, 2021). There was an obvious transition at the phylum level which showing that the relative abundance of Basidiomycota steadily increased, while the relative abundance of Ascomycota gradually decreased along with natural revegetation (Table 2).…”
Section: Discussionsupporting
confidence: 92%
“…For instance, Ascomycota prefer high-quality and simple substrates (e.g., low C:N; Thomson et al, 2015), and flourish in oligotrophic environments (Yang et al, 2019). Whereas, Basidiomycota are inclined to degrade low-quality and recalcitrant substrates (e.g., high C:N; Thomson et al, 2015;Llimós et al, 2021), and thrive in copiotrophic environments (Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, compared to plant-derived organic fertilizers, manure-derived organic fertilizers are abundant in N and P nutrients and contain more living microorganisms ( Xia et al, 2021 ). As a result, the response of the soil fungal community to organic fertilizers varied with the fertilizer type ( Ding et al, 2017 ; Llimos et al, 2021 ). The differences reflect in the diversity and species composition of the community as well as the tropic models ( Wang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…37,38 Microvirga is a symbiotic nitrogen-fixing bacterium, and its abundance usually increased only in the presence of plants and decreased after the addition of compost. 39 The use of nZVI mainly increased abundance of Lysobacter (5.3%) and Ramlibacter (2.7%), but decreased the abundance of Microvirga (1.2%). Lysobacter and Ramlibacter both belong to the bacterial phylum Proteobacteria (Table S2 †), and the abundance increase of these two bacterial genera might be related to the nZVI treatment and iron oxidation.…”
Section: Species Difference Analysismentioning
confidence: 96%